Case report: A rare homozygous variation in the ENPP1 gene, presenting with generalized arterial calcification of infancy in a Chinese infant - Lu, Pengtao; Chen, Jinglong; Chen, Mei; Wang, Ling; Xiang, Dandan; Yin, Jie; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2023)
Generalized arterial calcification of infancy (GACI) is a rare genetic disease characterized by arterial calcifications or stenoses and hypertension. GACI is caused by mutations in the ENPP1 or ABCC6 genes, and it often causes intrauterine or early infancy death. Here, we report a case of rare GACI caused by a homozygous variation in ENPP1, in a Chinese infant initially presenting with hypertension. The proband was an 8-month-old boy with in utero tricuspid valve calcification, presenting with hypertension at birth. Enhanced computed tomography revealed extensive arterial calcification. Genetic testing identified a homozygous variation in ENPP1 (c.783C > G p.Y261X), which led to the diagnosis of GACI. This mutation has been reported in only three Chinese patients, which all initially presented with hypophosphatemic rickets rather than GACI. This case enriches the clinical and genetic spectrum of ENPP1 mutations and reminds us that GACI should be considered in an infant presenting with hypertension and extensive arterial calcification, and that genetic testing should be performed.